2017
DOI: 10.1371/journal.pone.0175743
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes in the microcirculation of lepromatous leprosy patients - Observation using orthogonal polarization spectral imaging and laser Doppler flowmetry iontophoresis

Abstract: Leprosy is a chronic granulomatous infection of skin and peripheral nerves caused by Mycobacterium leprae and is considered the main infectious cause of disability worldwide. Despite the several studies regarding leprosy, little is known about its effects on microvascular structure and function in vivo. Thus, we have aimed to compare skin capillary structure and functional density, cutaneous vasomotion (spontaneous oscillations of arteriolar diameter), which ensures optimal blood flow distribution to skin capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…In other words, microvascular function in TT skin lesions was preserved. Using the same technique, our group demonstrated that LL (the other polar form of Leprosy) caused a significant impairment of endothelial dependent and independent vasodilatations, which evidence an expressive microvascular dysfunction in these patients [22]. Ultrastructural studies of skin biopsies of LL patients revealed endothelial infection by M. leprae [6,34].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In other words, microvascular function in TT skin lesions was preserved. Using the same technique, our group demonstrated that LL (the other polar form of Leprosy) caused a significant impairment of endothelial dependent and independent vasodilatations, which evidence an expressive microvascular dysfunction in these patients [22]. Ultrastructural studies of skin biopsies of LL patients revealed endothelial infection by M. leprae [6,34].…”
Section: Discussionmentioning
confidence: 95%
“…Decreased blood perfusion was also reported by our group in the other polar form of leprosy. In this recent study Treu and coworkers [22], using orthogonal polarization spectral imaging (OPS), showed that LL patients have a significant lower functional capillary density (number of perfused capillaries/mm 2 ) in their skin compared to healthy controls. In addition to functional capillary density, estimated by PVD, SDF allows the evaluation of FHI, which is the difference between the highest MFI and the lowest MFI divided by the mean MFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to development of anesthetic skin patch and peripheral nerve thickening [27][28][29] . The skin lesions thus developed due to nerve damage and loss of sensory perception has gross micro-vascular dysfunction and significant alterations in blood capillary network and these changes are attributed to inflammation 30 . Such altered blood flow may result in altered hydration levels of skin that changes in resident microbial community structure.…”
Section: Discussionmentioning
confidence: 99%
“…7 Treu et al showed lepromatous leprosy causes severe microvascular dysfunction and significant alterations in capillary structure. 8 Since microvascular dysfunction is a systemic process that occurs similarly in the entire body, 9 it is possible to consider that the impairment of microvascular function observed in the skin microvasculature also occurs in the coronary microcirculation, which results in heart failure.…”
Section: Discussionmentioning
confidence: 99%